A modifications of conjugate gradient method for unconstrained optimization problems - Alshorman, Omar; Mamat, Mustafa; Alhawarat, Ahmad; Revaie, Mohd (International Journal of Engineering and Technology, 2018)
The Conjugate Gradient (CG) methods play an important role in solving large-scale unconstrained optimization problems. Several studies have been recently devoted to improving and modifying these methods in relation to efficiency and robustness. In this paper, a new parameter of CG method has been proposed. The new parameter possesses global convergence properties under the Strong Wolfe-Powell (SWP) line search. The numerical results show that the proposed formula is more efficient and robust compared with Polak-Rribiere Ployak (PRP), Fletcher-Reeves (FR) and Wei, Yao, and Liu (WYL) parameters.Â Â